2022
DOI: 10.1177/00099228221118401
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Themes Depicted in Television Shows Targeted Toward Adolescents

Abstract: The American Academy of Pediatrics has previously expressed concerns about the thematic content of television (TV) and the amount of time children spend viewing TV. The objective of this study was to determine the positive and negative themes depicted in a select number of TV shows targeted toward adolescents. We analyzed the thematic content depicted in the first season of 26 Netflix TV shows. The mean occurrences/h for positive and negative themes were 39.53 and 47.20, respectively. The most common positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Psychological publications are more likely to identify triggers of aggressive attitudes that have to do with the bully’s family or social context [ 25 ]. On the other hand, there are works focused on analyzing the influence that certain specific factors have on the development of bullying attitudes, such as (i) television watching and the excessive use of video games with violent content [ 28 , 29 ]; (ii) parental behaviors of rejection, chaos, coercion or aggressiveness, which favor the development of bullying attitudes and, above all, cyberbullying in young people [ 27 ]; (iii) pressure from circles of friends and the social context [ 19 , 20 ]; or (iv) the attitude of teachers, which conditions the adoption of the role of bully or victim by students [ 30 ]. As a novel result of the present study, it was found that all these factors are present, in the opinions of teachers and psychologists, in the development of aggressive behavior in early childhood education, but the existence of an action plan against bullying conditions the perception of which factors are considered dominant, which, moreover, are also different among teachers and psychologists ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological publications are more likely to identify triggers of aggressive attitudes that have to do with the bully’s family or social context [ 25 ]. On the other hand, there are works focused on analyzing the influence that certain specific factors have on the development of bullying attitudes, such as (i) television watching and the excessive use of video games with violent content [ 28 , 29 ]; (ii) parental behaviors of rejection, chaos, coercion or aggressiveness, which favor the development of bullying attitudes and, above all, cyberbullying in young people [ 27 ]; (iii) pressure from circles of friends and the social context [ 19 , 20 ]; or (iv) the attitude of teachers, which conditions the adoption of the role of bully or victim by students [ 30 ]. As a novel result of the present study, it was found that all these factors are present, in the opinions of teachers and psychologists, in the development of aggressive behavior in early childhood education, but the existence of an action plan against bullying conditions the perception of which factors are considered dominant, which, moreover, are also different among teachers and psychologists ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These aspects can trigger the development of aggressive behaviors among children derived from possible exposure to hostile behavior or peer pressure [ 19 , 26 ]. Added to this is the emergence today of other dangers arising from increased exposure to online environments [ 26 , 27 ] that child psychologists describe as triggering defiant and hostile attitudes among minors [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%